2023
DOI: 10.1111/ijd.16780
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of necrobiosis lipoidica with secukinumab (Cosentyx): a case series

Abstract: Treatment of necrobiosis lipoidica with secukinumab (Cosentyx): a case series Dear Editor, Necrobiosis lipoidica (NL) is a chronic granulomatous disease with no current Food and Drug Administration-approved treatment. Previous published treatments have been small and inconsistent. IL-17 has been implicated in the pathogenesis of NL. 1 We report the use of secukinumab, a monoclonal antibody against IL-17A, for treating NL. Patients enrolled from April 3, 2019, to April 15, 2021, in an open label, proof of conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The discovery of a key role for TNF- α in granuloma formation in mouse models provides a theoretical basis for explaining the efficacy of TNF-α inhibitors in granulomatous inflammatory diseases such as NL [ 74 , 75 ]. Although medications in this class have had a beneficial effect on many patients, there were cases reported that did not respond to treatment or the treatment had to be discontinued due to the loss of efficacy or adverse effects [ 76 , 77 , 78 , 79 ]. This has necessitated the search for new drugs effective in the treatment of necrobiosis lipoidica.…”
Section: Treatment Standards and New Therapeutic Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of a key role for TNF- α in granuloma formation in mouse models provides a theoretical basis for explaining the efficacy of TNF-α inhibitors in granulomatous inflammatory diseases such as NL [ 74 , 75 ]. Although medications in this class have had a beneficial effect on many patients, there were cases reported that did not respond to treatment or the treatment had to be discontinued due to the loss of efficacy or adverse effects [ 76 , 77 , 78 , 79 ]. This has necessitated the search for new drugs effective in the treatment of necrobiosis lipoidica.…”
Section: Treatment Standards and New Therapeutic Optionsmentioning
confidence: 99%
“…Wakusawa et al, in sections taken from NL lesions, revealed the presence of granulomas containing significant amounts of IL-17-releasing cells; therefore, this cytokine was associated with NL [ 85 ]. Gibson et al described four clinical cases of patients with treatment-resistant NL who received subcutaneous secukinumab for 24 weeks [ 78 ]. All patients responded to treatment, but the clinical improvement varied between patients (from about 25% to about 90% improvement).…”
Section: Treatment Standards and New Therapeutic Optionsmentioning
confidence: 99%